The Gut and Blood Microbiome in IgA Nephropathy and Healthy Controls. Issue 8 (26th August 2021) - Shah, Neal B.; Nigwekar, Sagar U.; Kalim, Sahir; Lelouvier, Benjamin; Servant, Florence; Dalal, Monika; Krinsky, Scott; Fasano, Alessio; Tolkoff-Rubin, Nina; Allegretti, Andrew S.
Visual Abstract: Abstract: Key Points: A higher microbiome load, possibly originating from different body sites, may be playing a pathogenic role in IgA nephropathy. Several microbiome taxonomic differences between patients with IgA nephropathy and healthy controls are observed in blood and stool. Striking differences between the blood and gut microbiome confirm that the blood microbiome does not directly reflect the gut microbiome. Background: IgA nephropathy (IgAN) has been associated with gut dysbiosis, intestinal membrane disruption, and translocation of bacteria into blood. Our study aimed to understand the association of gut and blood microbiomes in patients with IgAN in relation to healthy controls. Methods: We conducted a case-control study with 20 patients with progressive IgAN, matched with 20 healthy controls, and analyzed bacterial DNA quantitatively in blood using 16S PCR and qualitatively in blood and stool using 16S metagenomic sequencing. We conducted between-group comparisons as well as comparisons between the blood and gut microbiomes. Results: Higher median 16S bacterial DNA in blood was found in the IgAN group compared with the healthy controls group (7410 versus 6030 16S rDNA copies/ μ l blood, P =0.04). α - and β -Diversity in both blood and stool was largely similar between the IgAN and healthy groups. In patients with IgAN, in comparison with healthy controls, we observed higher proportions of the class Coriobacteriia and species of the genera Legionella, Enhydrobacter, and Parabacteroides in blood, and species of the genera Bacteroides, Escherichia-Shigella, and some Ruminococcus in stool. Taxa distribution were markedly different between the blood and stool samples of each subject in both IgAN and healthy groups, without any significant correlation between corresponding gut and blood phyla. Conclusions: Important bacterial taxonomic differences, quantitatively in blood and qualitatively in both blood and stool samples, that were detected between IgAN and healthy groups warrant further investigation into their roles in the pathogenesis of IgAN. Although gut bacterial translocation into blood may be one of the potential sources of the blood microbiome, marked taxonomic differences between gut and blood samples in each subject in both groups confirms that the blood microbiome does not directly reflect the gut microbiome. Further research is needed into other possible sites of origin and internal regulation of the blood microbiome.